(x-3)+5=0

Simple and best practice solution for (x-3)+5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)+5=0 equation:


Simplifying
(x + -3) + 5 = 0

Reorder the terms:
(-3 + x) + 5 = 0

Remove parenthesis around (-3 + x)
-3 + x + 5 = 0

Reorder the terms:
-3 + 5 + x = 0

Combine like terms: -3 + 5 = 2
2 + x = 0

Solving
2 + x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + x = 0 + -2

Combine like terms: 2 + -2 = 0
0 + x = 0 + -2
x = 0 + -2

Combine like terms: 0 + -2 = -2
x = -2

Simplifying
x = -2

See similar equations:

| 20c=7+9x | | 3(x+6)+4(x+2)=12 | | 6x-4-3x-3=3 | | X^2-5x-y=0 | | 3h-2=35 | | 3(X/7)=24 | | (2x+4)(5x+5)= | | 2(3x-2)-3(x+1)=3 | | (C-2)(C-5)= | | y[n]-0.5*y[n-2]=0 | | 24/2=4/2x | | 44=2(4+3x)+2(4+5x) | | 2x(x+e)=3e(x+e) | | 162=2xsquared | | 4s^2+19=12s | | x/y=2.727272 | | 10x-x^2=5 | | 10x-y^2=5 | | 3+4x-10=17 | | N(14+6)=22 | | (a+1)(a*2+3a+1)= | | x^2-61.28x=2000 | | 15+3y=51-y-y-y | | 16-7m=30 | | 5-3y+5y=-8+6+9y | | -(x-1)=x-5 | | 64-32y=55-35y | | 27=5-2x | | 7+91x=52x+3 | | -2(x-5)=10-3x | | 6x-3x(x-1)=21 | | 2x^2+2y-1=0 |

Equations solver categories